Error Budget of the MEthane Remote LIdar missioN and Its Impact on the Uncertainties of the Global Methane Budget. Issue 20 (30th October 2018) - Bousquet, Philippe; Pierangelo, Clémence; Bacour, Cédric; Marshall, Julia; Peylin, Philippe; Ayar, Pradeebane Vaittinada; Ehret, Gerhard; Bréon, François‐Marie; Chevallier, Frédéric; Crevoisier, Cyril; Gibert, Fabien; Rairoux, Patrick; et al.
Abstract: MEthane Remote LIdar missioN (MERLIN) is a German‐French space mission, scheduled for launch in 2024 and built around an innovative light detecting and ranging instrument that will retrieve methane atmospheric weighted columns. MERLIN products will be assimilated into chemistry transport models to infer methane emissions and sinks. Here the expected performance of MERLIN to reduce uncertainties on methane emissions is estimated. A first complete error budget of the mission is proposed based on an analysis of the plausible causes of random and systematic errors. Systematic errors are spatially and temporally distributed on geophysical variables and then aggregated into an ensemble of 32 scenarios. Observing System Simulation Experiments are conducted, originally carrying both random and systematic errors. Although relatively small (±2.9 ppb), systematic errors are found to have a larger influence on MERLIN performances than random errors. The expected global mean uncertainty reduction on methane emissions compared to the prior knowledge is found to be 32%, limited by the impact of systematic errors. The uncertainty reduction over land reaches 60% when the largest desert regions are removed. At the latitudinal scale, the largest uncertainty reductions are achieved for temperate regions (84%) and then tropics (56%) and high latitudes (53%). Similar Observing System Simulation Experiments based on error scenarios for Greenhouse Gases Observing SATellite reveal that MERLIN should perform better than Greenhouse Gases Observing SATellite for most continental regions. The integration of error scenarios for MERLIN in another inversion system suggests similar results, albeit more optimistic in terms of uncertainty reduction. Plain Language Summary: Atmospheric methane is the second most important anthropogenic greenhouse gas. Its evolution in the atmosphere reflects the balance between its emissions and its sinks, both being still very uncertain. Observations and models are necessary to improve this situation and reduce the uncertainties associated to the global methane cycle, which is critical considering climate change. In this context, the MEthane Remote LIdar missioN (MERLIN) German‐French space satellite mission, scheduled for launch in 2023, will retrieve methane atmospheric columns. MERLIN products will be integrated into atmospheric models to improve estimates of methane emissions and sinks. In this paper, we establish the first complete error budget of the future MERLIN instrument and use it to estimate the reduction of uncertainties on methane emissions that can be expected once the satellite is launched. The two main findings are that the uncertainties should be reduced on average by 60% over land, where most methane emissions are located, and that MERLIN should perform better than the main methane sounder currently on orbit for most continental regions. Key Points: MERLIN is a German‐French space mission, scheduled for launch in 2023 that will retrieve methane atmospheric weighted columns The expected performances of MERLIN products to improve the estimation of methane emissions is assessed MERLIN should improve estimates of continental‐scale methane emissions by 60%, performing better than GOSAT for most regions